Podsole, Relief und Vegetation in Nordborneo - Stein, Norbert (ERDKUNDE, 1988)
In Northern Borneo there are large areas which are characterized by podzols, mainly of humus podzols. The main occurrences are correlated to the following relief units and substrata: 1) areas of Tertiary sandstones and sandstones and clays in inter-bedding, mostly on plateaus and planation surfaces, but also on slopes; 2) Quaternary fluvial terraces of sand and clay sediments in alternating stratification; 3) Quaternary marine deposits of various age and of differing distance from the present coast line. The genesis of podzols exists in the combination of various factors: sandy surface material, bisedimentary deposits (sand and clay), pore discontinuities, soil water regime controlled by relief position, and leaf litter resistant to fast decomposition. As the edaphic climax vegetation, heath forests reflect the ecological conditions of areas with podzols. Canopy structure, leaf size (microphylly), stem diameter, height of trees, and floristic composition of the various heath forest types are an adequate expression of the particular site factors. A comparison of water consumption curves of two forest types shows that even in the ever-wet equatorial tropics periods of water stress can occur and that the physiognomic structure of the heath forest can compensate for such a stress situation.